1994
DOI: 10.3177/jnsv.40.147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet High in Medium-Chain Triglyceride on Plasma Ketone, Glucose, and Insulin Concentrations in Enterectomized and Normal Rats.

Abstract: SummaryThe effects of dietary medium-chain triglyceride (MCT) on the concentration of plasma ketone bodies in enterectomized and normal rats were examined, together with the effects on plasma glucose, plasma immuno-reactive insulin, and liver function. Four groups of enter ectomized rats and four groups of normal rats were fed experimental diets containing 0, 6, 11, or 21% of MCT by weight for 6 days. All animals including normal rats received meal-feeding for 3h once a day. On day 3, concentration of plasma k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…It has been shown that, after a single dose of MCT, a slight hypoglycemia occurs (5). This change was not observed in our study and insulin and glucose levels did not differ significantly between the two groups as previously reported (9,29), which showed that in the case of moderate MCT content, no increase of ketone bodies concentration is observed.…”
Section: Discussionsupporting
confidence: 58%
“…It has been shown that, after a single dose of MCT, a slight hypoglycemia occurs (5). This change was not observed in our study and insulin and glucose levels did not differ significantly between the two groups as previously reported (9,29), which showed that in the case of moderate MCT content, no increase of ketone bodies concentration is observed.…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, determinations of 13 C excess in plasma phospholipid n-6 fatty acids allowed us to study 18:2n-6 metabolism in the two feeding groups. Since MCT feeding produces a slight hyperinsulinemic response (41,42), it might enhance ⌬5 and ⌬6 desaturase activity (43). However, the ratios of 13 C enrichments and tracer concentrations of precursor and product fatty acids were similar between the feeding groups, indicating no influence of MCT on the fractional conversion of 18:2n-6 toward LCP.…”
Section: Discussionmentioning
confidence: 83%
“…There was a significant decrease in circulating insulin concentrations in the MCT-fed weaner pigs. The effect of MCT supplementation on insulin secretion in adult human and rodent studies is equivocal [ 26 ], but the majority reports a slight hyperinsulinemic response [ 27 – 30 ]. In the pig, weaning is usually associated with a decrease in insulin due to the dietary energy deficit [ 31 ].…”
Section: Discussionmentioning
confidence: 99%